Unusual fatty acid substitution in lipids and lipopolysaccharides of Helicobacter pylori. - Geis, G (1990)
Cellular fatty acids, phospholipid fatty acids, and lipopolysaccharide fatty acids of four strains of Helicobacter pylori were analyzed by gas-liquid chromatography. The presence of myristic acid, palmitic acid, stearic acid, oleic acid, linoleic acid, 19-carbon cyclopropane fatty acid, beta-hydroxypalmitic acid, and beta-hydroxystearic acid was confirmed. In phospholipids, myristic acid and 19-carbon cyclopropane fatty acid were the major fatty acids. Hydroxy fatty acids and unsaturated fatty acids were not detected or occurred only in small amounts. The major fatty acids of lipopolysaccharides were stearic acid, beta-hydroxypalmitic acid, and beta-hydroxystearic acid. Unsaturated fatty acids and 19-carbon cyclopropane fatty acid were not found. The unusual compositions of H. pylori phospholipid and lipopolysaccharide fatty acids may have important implications for the taxonomy, physicochemical membrane properties, and biological activity of lipopolysaccharides.